2002
DOI: 10.1159/000066767
|View full text |Cite
|
Sign up to set email alerts
|

Possible Modulatory Role of Nitric Oxide in Lung Toxicity Induced in Rats by Chronic Administration of Bleomycin

Abstract: Background: The present study was undertaken to evaluate whether stimulation or inhibition of nitric oxide (NO) synthesis could affect lung toxicity induced by chronic administration of bleomycin (BLM). L-arginine (ARG) and NG-nitro-L-arginine methyl ester (L-NAME) were employed as NO precursor and NO synthesis inhibitor, respectively. Methods: BLM was administered intraperitoneally to male Wistar rats at a dose of 15 mg/kg, 3 times a week, for a total period of 4 weeks. ARG (500 mg/kg/day) and L-NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Pharmacological inhibitors of NOS, and also ablation of the gene for iNOS has been shown to reduce the development of the inflammatory response [47-49]. In addition, various studies have point out that iNOS play an important role in the pulmomary fibrosis induced by bleomycin [50-52]. Therefore, some study have also demonstrated that non-selective and partial selective iNOS inhibitor like aminoguanidine exert beneficial effect against lung injury induced by bleomycin [53-57].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibitors of NOS, and also ablation of the gene for iNOS has been shown to reduce the development of the inflammatory response [47-49]. In addition, various studies have point out that iNOS play an important role in the pulmomary fibrosis induced by bleomycin [50-52]. Therefore, some study have also demonstrated that non-selective and partial selective iNOS inhibitor like aminoguanidine exert beneficial effect against lung injury induced by bleomycin [53-57].…”
Section: Discussionmentioning
confidence: 99%
“…Bleomycin-induced pulmonary injury and lung fibrosis have been documented in studies using several animal models [4, 5]. These models have been widely used for studying the mechanisms involved in the progression of human pulmonary fibrosis and the impact of various drugs on this progression [6, 7]. The bleomycin induces the genesis of reactive oxygen species upon binding to DNA and iron, which in turn causes DNA damage [8].…”
Section: Introductionmentioning
confidence: 99%
“…This model has been widely used for studying the mechanisms involved in the progression of human pulmonary fibrosis and the impact of various drugs on this progression (Yara et al, 2001;El-Khatib, 2002).…”
Section: Introductionmentioning
confidence: 99%